Réponses

  • Omnes
  • Modérateur confirmé
2014-02-15T15:31:47+01:00
Salut,

A = (3x-5)(5-2x) - (3x-5)²
A = 15x - 6x² -25 + 10x - (9x² - 30x + 25)
A = 25x -6x² -25 -9x² + 30x - 25
A = 55x -15x² -50

A = (3x -5)(5-2x) - (3x-5)²
A = (3x-5)(5-2x - (3x-5))
A = (3x-5)(5-2x - 3x + 5)
A = (3x-5)(10 -5x)
A = 5(3x-5)(2-x)

A = 0
5(3x-5)(2-x) = 0
3x - 5 = 0
3x = 5
x = 5/3

2-x = 0
-x = -2
x = 2


2014-02-15T15:37:26+01:00
1) A=(3x-5)(5-2x)-(3x-5)^2=15x-6x^2-25+10x-(9x^2-30x+25)=-6x^2+25x-25-9x^2+30x-25=-15x^2+55x-50

2) A=(3x-5)(5-2x)-(3x-5)^2=(3x-5)(5-2x-(3x-5))=(3x-5)(5-2x-3x+5)=(3x-5)(-5x+10)=5(3x-5)(-x+2)

3) A=0 ---> 5(3x-5)(-x+2)=0 ---> 3x-5=0 ou -x+2=0 ---> x=5/3 ou x=2